2018
DOI: 10.14429/dlsj.3.12192
|View full text |Cite
|
Sign up to set email alerts
|

Poly (γ-) Glutamic Acid : A Promising Biopolymer

Abstract: Poly (γ-) glutamic acid (γ-PGA) is a polymer of L or D -glutamic acid units produced by microorganisms as a defense mechanism as an act of stress tolerance. Production of γ-PGA by microbial source has been gaining attention due to its low cost of production and varied application with high compatibility and high biodegradability. Its application ranges from food industry to waste water treatment. γ-PGA is a major constituent of Japanese foodnatto. γ-PGA has vast applications in food, pharmaceuticals, healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Composition of the fermentation medium is one of the most important determinants of both the production rate as well as the properties of γ-PGA produced by microbial fermentation [6]. The effect of medium composition was shown by Birrer et al [34] when the medium NaCl concentration was varied.…”
Section: Optimization Of Medium Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Composition of the fermentation medium is one of the most important determinants of both the production rate as well as the properties of γ-PGA produced by microbial fermentation [6]. The effect of medium composition was shown by Birrer et al [34] when the medium NaCl concentration was varied.…”
Section: Optimization Of Medium Compositionmentioning
confidence: 99%
“…Many types of researches, as a result, have focused on optimizing the growth condition of the producing bacteria, with a view to obtaining high yield and desirable molecular mass at a cheaper cost [3]. γ-PGA production and its properties depend largely on the nutrient composition of the fermentation medium as well as the pH of the medium, temperature and period of incubation, and the producing microbe [6].…”
Section: Introductionmentioning
confidence: 99%
“…Natural coagulants and flocculants are being replaced for chemical agents due to its extensive characters and source of origin (plants, animals, microbes and biowastes) (Ahmad et al, 2021;Ojewumi et al, 2021;Thirugnanasambandham and Karri, 2021). Anju et al (2017) and Kumar et al (2018) reported that polyglutamic acid (PGA) is a water-soluble and biodegradable anionic homopolyamide made up of L and D glutamic acid units with peptide bonds from peptide transformation, chemical synthesis, microbial fermentation and biotransformation. PGA is made up of non-essential aminoacids, especially glutamic acid (Dahiya et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, PGA with lower molecular weight serves as a drug carrier and cryoprotectant, while the L-glutamic acid enantiomer, acting as a humectant, is preferred for cosmetic uses. The conformation of PGA can vary between an α-helix, a β-sheet, a helix-to-random coil transition, or an enveloped aggregate, depending on factors like pH and polymer concentration [15]. Given its versatility, PGA finds utility across multiple sectors, including food, cosmetics, pharmaceuticals, and agriculture.…”
mentioning
confidence: 99%